Optimized design and manufacturing method and system for corrosion-resistant alloy structure of dock folding device
Through numerical simulation and experiments, the micro -structure and surface freedom of the device alloy of the dock folding the device is used to prepare ultra -hydrophobic alloys, solve the problem of easy corrosion of the dock folding device in the seawater environment, and improve the corrosion resistance and service life.
Patent Information
- Application Number
- CN202411381633.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Dock folding devices are prone to corrosion in seawater environments and affect their service life. Especially hydraulic devices need to withstand high-pressure environments, which further affect their structural strength and corrosion resistance.
The evolution of the micro -organizations of the section of the section through the numerical simulation alloy section, regulating the micro -structures and surface free energy parameters of the alloy, combining the corrosive environment and stress boundary conditions, calculating the corrosion potential and current density of the alloy, screening high corrosion -resistant alloys, and and. Prepare hydrophobic alloys through 3D printing and fluorosiline.
The corrosion resistance of the alloy structure is improved, the service life is extended, the dependence on post-processing methods is reduced, and the performance can be directly controlled during the forming process.
Smart Images

Figure CN119358135A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of corrosion-resistant alloy materials, and in particular to a corrosion-resistant alloy structure optimization design and manufacturing method and system for a dock folding device. Background Art
[0002] With the development of shipbuilding and marine engineering technology, dock folding devices are located in docks. As important facilities for the manufacture, maintenance and repair of marine engineering equipment such as ships, dock folding devices are prone to surface corrosion in seawater environments for a long time, which affects their service life. In particular, the hydraulic components of dock folding devices also need to withstand high pressure environments inside and outside, which further affects their structural strength and corrosion resistance. Therefore, it is necessary to study the surface damage and corrosion process of alloy structural parts, especially hydraulic components, under uniform external high pressure conditions in seawater, explore the microscopic mechanism analysis technology of material failure, reveal the inhibition mechanism of alloy processing parameters on the (electro)chemical corrosion and leakage of materials, and develop effective methods for in-situ regulation of surface anti-corrosion and anti-seepage performance during forming, laying the foundation for the corrosion-resistant optimization design and manufacturing of alloy structures. Summary of the invention
[0003] In view of the above defects or improvement needs of the prior art, the present invention provides a method and system for optimizing the design and manufacturing of a corrosion-resistant alloy structure of a dock folding device, which can combine theoretical simulation and experiment to clarify the intrinsic relationship between the construction method-microstructure, surface free energy-hydrophobicity-corrosion resistance of the corrosion-resistant alloy, provide a basis for the optimized design of the alloy, and improve the corrosion resistance of the alloy structure.
[0004] To achieve the above purpose, the present invention adopts the following technical solution.
[0005] In some embodiments, a method for optimizing the design and manufacturing of a corrosion-resistant alloy structure of a dock folding device is provided, the method comprising:
[0006] Through numerical simulation methods, the evolution of alloy cross-section microstructure in seawater is captured;
[0007] By adjusting the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions are calculated to measure the corrosion resistance of the alloy;
[0008] Establish the quantitative relationship between alloy microstructure, surface free energy and corrosion resistance;
[0009] Screening alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy to obtain target microstructure parameters and target surface free energy parameters of the alloys;
[0010] According to the target microstructure parameters, using preset 3D printing conditions, constructing an alloy having a target microstructure through metal 3D printing;
[0011] Using a preset pretreatment condition, a dense oxide film is modified on the surface of the alloy by a pretreatment method;
[0012] Using preset fluorosilane modification conditions, the alloy with the oxide film is modified by fluorosilane, thereby preparing a super-hydrophobic alloy;
[0013] The microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy;
[0014] The alloy preparation conditions are optimized according to the influence rules.
[0015] In some embodiments, the alloy includes one or more of aluminum alloy, copper alloy, stainless steel, and titanium alloy.
[0016] In some embodiments, the numerical simulation method includes a molecular dynamics simulation method and a finite element simulation method.
[0017] In some embodiments, the corrosion environment and stress boundary conditions include corrosion medium, temperature, and stress boundary conditions.
[0018] In some embodiments, the pretreatment method includes at least one of micro-arc oxidation, anodization, and hydrothermal oxidation; and the fluorosilane includes perfluorooctyltriethoxysilane or perfluorodecyltrichlorosilane.
[0019] In some embodiments, the microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by a detection device, including:
[0020] Detecting the microstructural parameters of the super-hydrophobic alloy by scanning electron microscopy or metallographic microscopy;
[0021] The functional group content and the oxide film composition parameters of the super-hydrophobic alloy are detected by X-ray photoelectron spectrometer, X-ray diffractometer and infrared spectrum;
[0022] The seawater contact angle and surface free energy of the superhydrophobic alloy are tested by a contact angle tester.
[0023] In some embodiments, the method further comprises:
[0024] The corrosion resistance of the super-hydrophobic alloy is tested by a salt spray full immersion test and an electrochemical test, and the charge transfer resistance is characterized by testing and simulating the electrochemical impedance spectroscopy of different super-hydrophobic alloys;
[0025] The steady-state electrochemical behavior was analyzed by potentiodynamic polarization test, and the corrosion potential, corrosion current density, cathode Tafel slope, and anode Tafel slope parameters of different superhydrophobic alloys were compared.
[0026] Analyze the influence of hydrophobicity on corrosion behavior, and thus obtain the correlation between alloy construction method-microstructure, surface free energy-hydrophobicity-corrosion resistance;
[0027] The target preparation conditions are optimized according to the correlation.
[0028] In some embodiments, a 3.5% by mass NaCl solution with a pH of 8 is used to simulate a seawater environment as a corrosion resistance test medium for an electrochemical test.
[0029] In some embodiments, the method further comprises:
[0030] By adjusting the heat source and process parameters to change the solidification condition of the alloy microstructure, or by changing the scanning strategy and forming angle to induce the formation of different microstructure orientations, the relationship between process parameters-microstructure-wear resistance and strength is analyzed, and combined with the plastic failure mechanism of the microstructure, the microstructure is induced with performance as the goal, thereby achieving in-situ enhancement of wear resistance and strength.
[0031] In some embodiments, a corrosion-resistant alloy structure optimization design and manufacturing system for a dock folding device is also provided, the system comprising:
[0032] Numerical simulation module, which captures the evolution of alloy cross-section microstructure in seawater through numerical simulation methods;
[0033] The module for establishing the quantitative relationship of corrosion resistance calculates the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions by regulating the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, which is used to measure the corrosion resistance of the alloy; establishes the quantitative relationship between the alloy microstructure, surface free energy and corrosion resistance;
[0034] The target parameter acquisition module screens alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy, and obtains the target microstructure parameters and target surface free energy parameters of the alloys;
[0035] A 3D printing module, according to the target microstructure parameters, uses preset 3D printing conditions to construct an alloy with a target microstructure through metal 3D printing;
[0036] A pretreatment module, using preset pretreatment conditions and a pretreatment method to modify a dense oxide film on the surface of the alloy;
[0037] A modification module, using preset fluorosilane modification conditions to modify the alloy with the oxide film by fluorosilane, thereby preparing a super-hydrophobic alloy;
[0038] The detection module detects the microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy through the detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy;
[0039] The optimization module optimizes the alloy preparation conditions according to the influencing rules.
[0040] Compared with the prior art, the beneficial effects of the present invention are:
[0041] In some embodiments of the present application, molecular dynamics simulation, finite element simulation and other methods are used to capture the evolution of the microstructure of the alloy cross section in seawater. By adjusting the model and material parameters such as the alloy microstructure, surface free energy, phase composition, and boundary conditions such as corrosive medium, temperature, and stress, the corrosion potential, corrosion current density, and charge transfer resistance of the alloy under different conditions are calculated to measure the corrosion resistance of the alloy. A quantitative relationship between the alloy microstructure, surface free energy, and its corrosion resistance is established, and alloys with high corrosion potential and low corrosion current density and their corresponding microstructure and surface free energy are screened.
[0042] On this basis, metal 3D printing was used to construct a titanium alloy with a specific microstructure, and a dense oxide film was modified on its surface through pretreatment methods such as micro-arc oxidation, anodization, and hydrothermal oxidation. The alloy with an oxide film was modified by fluorosilanes such as perfluorooctyltriethoxysilane and perfluorodecyltrichlorosilane, thereby realizing the preparation of a superhydrophobic alloy.
[0043] Combining theoretical simulation and experiments, the intrinsic relationship between the construction method of corrosion-resistant alloys, microstructure, surface free energy, hydrophobicity and corrosion resistance was obtained, providing guidance for alloy modification design.
[0044] By directly regulating the performance during the part forming process, parts with high surface wear resistance and high strength can be directly obtained, minimizing or eliminating the dependence of metal additive manufacturing parts on post-processing methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 The figure is a schematic diagram of the overall process of the alloy structure optimization design and manufacturing method according to one embodiment of the present invention.
[0046] Figure 2 Schematic diagram of the corrosion mechanism of an alloy structure under elastic stress according to an embodiment of the present invention.
[0047] Figure 3 Schematic diagram of the corrosion mechanism of an alloy structure under plastic stress according to an embodiment of the present invention.
[0048] Figure 4 The present invention is a schematic flow chart of a method for manufacturing corrosion-resistant alloy structure surface according to an embodiment of the present invention.
[0049] Figure 5 This is a schematic diagram of a corrosion-resistant alloy structure optimization design and manufacturing system for a dock folding device according to an embodiment of the present invention.
[0050] Figure 6 A schematic diagram of an electronic device according to an embodiment of the present invention. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0052] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0053] The internal microstructure of alloys manufactured based on SLM (Selective laser melting) is different from that of alloys produced by traditional processing technology, which leads to certain differences in the mechanical properties and corrosion resistance of the two. In addition, seawater has aggressive ions and a certain hydrostatic pressure. Many studies have shown that hydrostatic pressure accelerates the corrosion process of alloys. This water pressure is balanced and has a very different effect from the effect of tensile or compressive stress on corrosion. Hydrostatic pressure has two effects on the shell structure of the alloy: one is to provide internal stress that deforms the material; the other is to accelerate the electrochemical process at the metal / solution interface. Therefore, hydrostatic pressure will produce an unfavorable synergistic effect on the metal surface and have a significant impact on the stress corrosion sensitivity of the metal. Microstructure and composition adjustments will introduce defects, promote galvanic corrosion, and lead to a decrease in corrosion resistance. In a seawater environment, these shortcomings may be amplified. At the same time, these additional elements introduced by metallography will inevitably be incorporated into the passivation film during the passivation process.
[0054] The surface of the dock folding device is prone to corrosion in the seawater environment for a long time, which affects its service life. In addition, structural parts such as hydraulic components and supporting components also need to bear high pressure. Therefore, it is necessary to determine the method of observing the surface damage and corrosion process of structural parts under high-pressure seawater conditions, explore the microscopic mechanism analysis technology of material failure, reveal the inhibition mechanism of process parameters such as laser scanning path on the (electro)chemical corrosion and leakage of the material surface, and develop effective methods for in-situ regulation of surface anti-corrosion and anti-seepage properties during forming, laying the foundation for the corrosion-resistant design and application of alloy structures of dock folding devices.
[0055] Figure 1 This is a schematic diagram of the overall process of the alloy structure optimization design and manufacturing method according to one embodiment of the present invention. Figure 1 The present invention provides a method for optimizing the design and manufacturing of a corrosion-resistant alloy structure of a dock folding device, the method comprising:
[0056] Through numerical simulation methods, the evolution of alloy cross-section microstructure in seawater is captured;
[0057] By regulating the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions are calculated to measure the corrosion resistance of the alloy; in some embodiments, the corrosion environment and stress boundary conditions include corrosive medium, temperature and stress boundary conditions;
[0058] Establish the quantitative relationship between alloy microstructure, surface free energy and corrosion resistance;
[0059] Screening alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy to obtain target microstructure parameters and target surface free energy parameters of the alloys;
[0060] According to the target microstructure parameters, using preset 3D printing conditions, constructing an alloy having a target microstructure through metal 3D printing;
[0061] Using preset pretreatment conditions, a dense oxide film is modified on the surface of the alloy by a pretreatment method; in some embodiments, the pretreatment method includes at least one of micro-arc oxidation, anodization, and hydrothermal oxidation;
[0062] Using preset fluorosilane modification conditions, the alloy with the oxide film is modified by fluorosilane to prepare a super-hydrophobic alloy; in some embodiments, the fluorosilane includes perfluorooctyltriethoxysilane or perfluorodecyltrichlorosilane;
[0063] The microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy;
[0064] The alloy preparation conditions are optimized according to the influence rules.
[0065] In some embodiments of the present application, the failure mechanism of stress corrosion of alloys in seawater environment and the mechanism of degradation of passivation film caused by environmental sensitivity of alloy elements are explored to guide the phase and composition design of corrosion-resistant alloys in high-pressure environment, and analyze the relationship between the phase composition, microstructure, corrosion behavior and mechanical properties of the alloy.
[0066] In some embodiments of the present application, the alloy includes one or more of aluminum alloy, copper alloy, stainless steel, and titanium alloy. For example, the supporting body fixing structure of the folding device can be stainless steel, the material of the docking pier that can be folded and erected includes aluminum alloy or stainless steel, the precision valve body and hydraulic components can be copper alloy or titanium alloy, and the pulley is stainless steel.
[0067] The main component of the alloy passivation film is the oxide film. Figure 2 Schematic diagram of the corrosion mechanism of an alloy structure under elastic stress according to an embodiment of the present invention. Figure 2 Taking titanium alloy as an example, the outermost layer of the oxide film is mainly composed of TiO 2 (Ti 4+ ), while the part close to the alloy matrix is composed of Ti 2 O 3and TiO. Under the coupling effect of elastic stress and electrochemical corrosion, the corrosive ions tend to preferentially adhere to the defects on the surface of the alloy passivation film, resulting in high current density at certain local locations within the passivation film, and local areas are more susceptible to pitting corrosion. On the one hand, elastic stress mainly causes dislocation or even rupture of the passivation film, which leads to increased stress corrosion at the interface between the metal matrix and the corrosive medium. On the other hand, elastic stress causes metal deformation, making the alloy prone to pit formation, especially under irregular geometries and specific load conditions, which in turn triggers pitting corrosion.
[0068] In some embodiments of the present application, the numerical simulation method includes a molecular dynamics simulation method and a finite element simulation method. The numerical simulation method is used to capture the evolution of the microstructure of the alloy cross section in seawater.
[0069] Specifically, in the process of modeling, electrochemical reactions, the transfer of chemical substances, deformation of metal corrosion, and precipitation produced during corrosion can be considered. The finite element method is used to solve the internal reaction and transport problems of the corrosion reaction system. The calculations involving the resulting partial differential equations (PDEs) are performed using the Comsol software program, which helps to solve such nonlinear problems. The electrochemical reactions included in the model mainly include:
[0070] Ti+4H + →Ti 4+ +2H 2
[0071] Ti+2H 2 O→TiO 2 +2H 2
[0072] The conservation equation of matter:
[0073] The corrosion reaction system and its environment may include the following ion species: H + OH - 、Na + , Cl - 、Ti、Ti(OH) 2+ 、Ti(OH) 3+ 、Ti(OH) 4+ The Nernst-Planck equation includes diffusion and electromigration and is the governing equation for different species in a solution. The concentration change formula for each substance i in a solution is as follows:
[0074]
[0075] Where c i is the concentration of substance i, t is the time, D i is the diffusion coefficient, z iis the charge number, F is the Faraday constant, φ is the electrolyte potential, R is the gas constant, T is the temperature, R i is the source item.
[0076] Charge conservation equation:
[0077] ∑z i c i =0
[0078] Electrochemical parameters, including equilibrium potential, exchange current density, and Tafel slope of the redox reaction used in the simulation are known and optionally determined.
[0079] Figure 3 Schematic diagram of the corrosion mechanism of an alloy structure under plastic stress according to an embodiment of the present invention. Figure 3 In some embodiments of the present application, two major types of stress corrosion mechanisms are considered: anodic dissolution at the crack tip and hydrogen embrittlement. When an alloy is subjected to applied stress in a corrosive medium, if the corrosion rate is not severe enough to passivate the crack tip, the crack will extend into the metal and eventually lead to mechanical failure. The second mechanism is hydrogen-assisted cracking. After the hydrogen precipitation cathodic reaction absorbs hydrogen atoms near the crack tip, it will penetrate the interior of the alloy and promote the embrittlement of the crack tip. Through the numerical simulation method of the present application, the plastic deformation in the crack tip area where corrosion occurs can be simulated more scientifically and objectively.
[0080] Alloys such as titanium alloys and aluminum alloys have advantages such as low density and high strength, but show electrochemical corrosion sensitivity in marine environments. By constructing a super-hydrophobic layer on the alloy surface, it can be avoided from contacting with the electrolyte solution and improving corrosion resistance. The super-hydrophobicity of the super-hydrophobic layer is closely related to material parameters such as alloy microstructure and surface free energy. In some embodiments of the present application, numerical simulation means are used to explore the corrosion resistance mechanism of alloys from a microscopic scale, and the influence of alloy microstructure, surface free energy and its corrosion resistance is quantitatively described to guide the optimization of alloy parameters.
[0081] In some embodiments of the present application, based on the theoretical model, an alloy structure with a specific microstructure is manufactured by metal 3D printing, and its surface free energy is regulated by means of fluorosilane modification and the like. The influence of 3D printing conditions such as light intensity and printing speed and pretreatment methods, and fluorosilane modification conditions such as solution concentration and reaction temperature on the alloy microstructure and surface free energy are obtained. Combining theory and experiment, the alloy structure with the best corrosion resistance is optimized, and the intrinsic relationship and mechanism of action of processing conditions-microstructure, surface free energy-hydrophobicity-corrosion resistance are summarized.
[0082] According to the Cassie-baxter model, to construct an alloy with super hydrophobicity, two basic conditions must be met: one is that the alloy surface must have a fine microstructure, and the other is that its surface free energy must be less than the surface free energy of water. Metal 3D printing can finely control the surface microstructure of the alloy, and is one of the ideal additive manufacturing methods for constructing super hydrophobic alloys. At the same time, fluorosilane modification can effectively reduce the surface free energy of the alloy by modifying the fluorinated alkyl chain. In the embodiment of the present application. By quantifying the relationship between the super hydrophobicity and corrosion resistance of the alloy, the influence of microstructure and surface free energy on corrosion resistance is obtained, thereby optimizing the alloy 3D printing conditions and fluorosilane modification conditions.
[0083] Specifically, in some embodiments of the present application, molecular dynamics simulation, finite element simulation and other methods are used to capture the evolution of the microstructure of the alloy cross section in seawater. By adjusting the model and material parameters such as the alloy microstructure, surface free energy, phase composition, and boundary conditions such as corrosive medium, temperature, and stress, the corrosion potential, corrosion current density, and charge transfer resistance of the alloy under different conditions are calculated to measure the corrosion resistance of the alloy. A quantitative relationship between the alloy microstructure, surface free energy, and its corrosion resistance is established, and alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energies are screened.
[0084] Figure 4 This is a schematic diagram of a method for manufacturing a corrosion-resistant alloy structure surface according to an embodiment of the present invention. Figure 4 On this basis, metal 3D printing was used to construct a titanium alloy with a specific microstructure, and a dense oxide film was modified on its surface through pretreatment methods such as micro-arc oxidation, anodization, and hydrothermal oxidation. The alloy with an oxide film was modified by fluorosilanes such as perfluorooctyltriethoxysilane and perfluorodecyltrichlorosilane, thereby realizing the preparation of a superhydrophobic alloy.
[0085] In some embodiments, the microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by a detection device, including:
[0086] Detecting the microstructural parameters of the super-hydrophobic alloy by scanning electron microscopy or metallographic microscopy;
[0087] The functional group content and the oxide film composition parameters of the super-hydrophobic alloy are detected by X-ray photoelectron spectrometer, X-ray diffractometer and infrared spectrum;
[0088] The seawater contact angle and surface free energy of the superhydrophobic alloy are tested by a contact angle tester.
[0089] In the embodiments of the present application, the microstructure of the titanium alloy is characterized by scanning electron microscope, metallographic microscope, etc., the functional group content, oxide film composition and other parameters of the titanium alloy are characterized by X-ray photoelectron spectrometer, X-ray diffractometer, infrared spectrum, etc., the seawater contact angle and surface free energy are characterized by contact angle tester, the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy are explored, and the optimal preparation conditions are optimized.
[0090] In some embodiments, the method further comprises:
[0091] The corrosion resistance of the super-hydrophobic alloy was tested by a salt spray full immersion test and an electrochemical test, and the charge transfer resistance was characterized by testing and simulating the electrochemical impedance spectra of different super-hydrophobic alloys; the steady-state electrochemical behavior was analyzed by a potentiodynamic polarization test, and the corrosion potential, corrosion current density, cathode Tafel slope, and anode Tafel slope parameters of different super-hydrophobic alloys were compared; specifically, a 3.5% by mass NaCl solution with a pH of 8 was used to simulate a seawater environment as a corrosion resistance test medium for the electrochemical test;
[0092] Analyze the influence of hydrophobicity on corrosion behavior, and thus obtain the correlation between alloy construction method-microstructure, surface free energy-hydrophobicity-corrosion resistance;
[0093] The target preparation conditions are optimized according to the correlation.
[0094] In the embodiments of the present application, the corrosion resistance of the titanium alloy sample is tested by a salt spray full immersion test and an electrochemical test. A 3.5% NaCl solution with a pH of 8 is used to simulate the seawater environment as an electrochemical corrosion test medium. The charge transfer resistance is characterized by testing and simulating the electrochemical impedance spectrum of different alloy samples, and the steady-state electrochemical behavior is analyzed by a potentiodynamic polarization test. The corrosion potential, corrosion current density, cathode Tafel slope, anode Tafel slope and other parameters of different samples are compared to analyze the influence of hydrophobicity on corrosion behavior. Finally, combining theoretical simulation and experiment, the intrinsic relationship between the construction method of corrosion-resistant alloys, microstructure, surface free energy, hydrophobicity and corrosion resistance is obtained, providing guidance for alloy modification design.
[0095] In some embodiments, the method further comprises:
[0096] By adjusting the heat source and process parameters to change the solidification condition of the alloy microstructure, or by changing the scanning strategy and forming angle to induce the formation of different microstructure orientations, the relationship between process parameters-microstructure-wear resistance and strength is analyzed, and combined with the plastic failure mechanism of the microstructure, the microstructure is induced with performance as the goal, thereby achieving in-situ enhancement of wear resistance and strength.
[0097] In the process of metal additive manufacturing, a high-energy laser beam rapidly heats the metal material to above the melting point to become liquid metal, forming a liquid molten pool. As the laser moves, the molten metal material will solidify rapidly. Due to the point-by-point, line-by-line, and surface-by-surface processing methods, the material will repeatedly undergo rapid melting and rapid solidification. The process parameters of the forming process determine the energy absorption of the material during the sintering process and affect the melting, wetting and spreading behavior of the powder. Therefore, defects such as pores, spheroidization and holes often appear in metal additive manufacturing parts. The existence of these defects has an adverse effect on the wear resistance and strength of the parts. Reasonable selection of process parameters can minimize the occurrence of defects, but for metal additive manufacturing parts, their wear resistance and strength do not meet the standards of industrial applications. It is still necessary to further improve the material properties to meet the needs of practical applications.
[0098] For parts processed by traditional methods, some physical and chemical surface technologies are often used to improve their surface properties. Some surface post-treatment methods have been proven to effectively improve the wear resistance of metal additive manufacturing parts. These methods include laser polishing, mechanical grinding, sandblasting, surface texturing, coating, nitriding, surface rolling, heat treatment and some other surface modification methods. The strength of metal additive manufacturing parts is mainly enhanced by heat treatment. Among these methods, mechanical grinding, sandblasting and surface rolling belong to cold plastic deformation methods, which mainly apply compressive stress to the surface layer of the sample through external loads, so that the microstructure below the surface of the sample is refined, thereby improving wear resistance. Laser polishing, heat treatment and nitriding change the microstructure or composition of the sample through the action of heat. Coating directly covers the original sample surface with a material with higher wear resistance, thereby changing the microstructure of the sample surface. For the realization of these traditional post-processing methods, processing equipment other than metal additive manufacturing forming equipment is usually required to complete them. The process of different post-processing methods is relatively complicated. Taking DC-USRP as an example, its process parameters include spindle speed, rolling head diameter, rolling force, amplitude, ultrasonic frequency, etc. For nitriding process, it includes nitriding temperature, gas ratio, nitriding time, voltage, etc. For the processing of different materials, especially metal additive manufacturing materials, due to their unique microstructure, necessary process optimization and regulation are required. At the same time, the complex process of post-processing greatly increases the production cost and cycle of parts. More importantly, many post-processing methods can only process some regular shapes such as rods and planes due to their own process limitations. For complex structures such as integrated hydraulic component structures, the post-processing processing of irregular curved surfaces, inner holes and other structures is difficult. For heat treatment, although there is no restriction on the structure of parts, the heat treatment process will cause deformation of parts, affect the dimensional accuracy of parts, and may cause difficulties in the assembly of precision parts.
[0099] Wear resistance and strength are ultimately the embodiment of the material's ability to resist plastic deformation, and the material's ability to resist plastic deformation depends largely on the microstructure. Microstructures such as phase composition, grain size and morphology, and segregation of elements greatly affect the performance of parts. In the embodiments of the present application, the performance of parts can be regulated by manipulating and optimizing the microstructure. Specifically, by adjusting the heat source and process parameters to change the solidification of the microstructure, or by changing the scanning strategy, forming angle, etc. to induce the formation of different microstructure orientations, and then determine the relationship between process parameters-microstructure-performance (wear resistance and strength). On the basis of an in-depth analysis of the plastic failure mechanism of the microstructure, the microstructure is induced with performance as the goal, thereby achieving in-situ enhancement of the wear resistance and strength of the parts and reducing subsequent unnecessary processing.
[0100] In the embodiments of the present application, the characteristics of metal additive manufacturing are fully utilized. Compared with traditional processing methods, metal additive manufacturing provides a great control space for heat sources. This characteristic allows direct microstructural regulation during the part forming process. In the embodiments of the present application, the performance is directly regulated during the part forming process, so as to directly obtain parts with high surface wear resistance and high strength, and the dependence of metal additive manufacturing parts on post-processing methods is reduced or eliminated as much as possible.
[0101] In some embodiments of the present application, for wear resistance, a nano scratch test is used to reveal the wear failure mechanism of the material. Compared with reciprocating or rotating friction and wear tests, the scratch test method is more suitable for exploring the wear failure behavior of the alloy. By setting different load sizes, the wear resistance of different microstructures is tested respectively, and the corresponding wear amount is measured and calculated by confocal microscopy to evaluate the wear resistance difference of different microstructures. A scanning electron microscope is used to observe the wear scar morphology, observe the plastic damage of the material surface, analyze the deformation behavior of different microstructures, and observe the generation and expansion of crack defects, so as to obtain the wear failure mechanism of the cellular substructure, grain morphology and grain orientation under different loads.
[0102] In some embodiments of the present application, the strength is tested using a tensile testing machine according to the test standard GB / T 228.1-2010. Before the test, the grains in the deformation area are calibrated, the morphology of the grains under different strains is measured, and the plastic deformation behavior of the grains during the stretching process is analyzed by comparing the morphology under different strains. On the other hand, a scanning electron microscope is used to observe the fracture of the sample after fracture to analyze the influence of different poroid substructures and molten pools on the generation of defects.
[0103] In the embodiments of the present application, by directly regulating the performance during the part forming process, parts with high surface wear resistance and high strength are directly obtained, thereby reducing or eliminating the dependence of metal additive manufacturing parts on post-processing methods as much as possible.
[0104] Figure 5 This is a schematic diagram of a corrosion-resistant alloy structure optimization design and manufacturing system for a dock folding device according to an embodiment of the present invention. Figure 5 In some embodiments of the present application, a corrosion-resistant alloy structure optimization design and manufacturing system for a dock folding device is also provided, the system comprising:
[0105] Numerical simulation module, which captures the evolution of alloy cross-section microstructure in seawater through numerical simulation methods;
[0106] The module for establishing the quantitative relationship of corrosion resistance calculates the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions by regulating the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, which is used to measure the corrosion resistance of the alloy; establishes the quantitative relationship between the alloy microstructure, surface free energy and corrosion resistance;
[0107] The target parameter acquisition module screens alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy, and obtains the target microstructure parameters and target surface free energy parameters of the alloys;
[0108] A 3D printing module, according to the target microstructure parameters, uses preset 3D printing conditions to construct an alloy with a target microstructure through metal 3D printing;
[0109] A pretreatment module, using preset pretreatment conditions and a pretreatment method to modify a dense oxide film on the surface of the alloy;
[0110] A modification module, using preset fluorosilane modification conditions to modify the alloy with the oxide film by fluorosilane, thereby preparing a super-hydrophobic alloy;
[0111] The detection module detects the microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy through the detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy;
[0112] The optimization module optimizes the alloy preparation conditions according to the influencing rules.
[0113] The corrosion-resistant alloy structure optimization design and manufacturing system of the dock folding device is used to realize the above-mentioned manufacturing method.
[0114] The corrosion-resistant alloy structure optimization design and manufacturing system of the dock folding device can be an integrated manufacturing platform, which can include electronic equipment.
[0115] refer to Figure 6 In some embodiments, an electronic device is also provided, comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein when the processor executes the program, the numerical simulation, analysis, or control step in any of the above-described methods is implemented.
[0116] At the hardware level, the electronic device includes a processor, an internal bus, a network interface, a memory, and a non-volatile memory, and may also include other hardware required for the business. The processor reads the corresponding computer program from the non-volatile memory into the memory and then runs it to achieve the above Figure 1 The alloy structure optimization design and manufacturing method described above. Of course, in addition to the software implementation, this specification does not exclude other implementation methods, such as logic devices or a combination of software and hardware, etc., that is to say, the execution subject of the following processing flow is not limited to each logic unit, but can also be hardware or logic devices. It can be understood that it is only necessary to program the method flow slightly in a hardware description language and program it into an integrated circuit to obtain a hardware circuit that implements the logical method flow.
[0117] The above method can be implemented by a controller in any appropriate manner. For example, the controller can take the form of a microprocessor or processor and a computer-readable medium storing a computer-readable program code (such as software or firmware) that can be executed by the (micro)processor, a logic gate, a switch, an application-specific integrated circuit (ASIC), a programmable logic controller, and an embedded microcontroller. Examples of controllers include but are not limited to microcontrollers. The memory controller can also be implemented as part of the control logic of the memory. It is understandable that in addition to implementing the controller in a purely computer-readable program code manner, the controller can be implemented in the form of a logic gate, a switch, an application-specific integrated circuit, a programmable logic controller, and an embedded microcontroller by logically programming the method steps. Therefore, this controller can be considered as a hardware component, and the devices included therein for implementing various functions can also be regarded as structures within the hardware component. Or even, the devices for implementing various functions can be regarded as both software modules for implementing the method and structures within the hardware component.
[0118] The systems, devices, modules or units in the above embodiments may be implemented by computer chips or entities, or by products with certain functions. A typical implementation device is a computer. Specifically, the computer may be, for example, a personal computer, a laptop computer, a cellular phone, a camera phone, a smart phone, a personal digital assistant, a game console, a tablet computer, a wearable device, or a combination of any of these devices.
[0119] For the convenience of description, the above device is described by dividing it into various modules according to its functions. Of course, when implementing this specification, the functions of each module can be implemented in the same or multiple software and / or hardware.
[0120] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems, or computer program products. Therefore, this specification may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the application may adopt the form of a computer program product implemented on one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) that contain computer-usable program code.
[0121] The present application is described with reference to the flowcharts and / or block diagrams of the methods, devices (systems), and computer program products according to the embodiments of the present specification. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of the processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0122] In some embodiments, a computer-readable storage medium is further provided, wherein the storage medium stores a computer program, and when the computer program is executed by a processor, any of the above-described methods is implemented.
[0123] In some embodiments, these computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to work in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture including an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.
[0124] In some embodiments, these computer program instructions may also be loaded onto a computer or other programmable data processing device so that a series of operation steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process in the computer or other programmable device. Figure 1 A process or multiple processes and / or boxes Figure 1 The steps for the functions specified in one or more boxes.
[0125] In some embodiments, the computing device includes one or more processors (CPU), input / output interfaces, network interfaces, and memory.
[0126] In some embodiments, the memory may include non-permanent storage in a computer-readable medium, in the form of random access memory (RAM) and / or non-volatile memory, such as read-only memory (ROM) or flash RAM. The memory is an example of a computer-readable medium.
[0127] In some embodiments, computer-readable media include permanent and non-permanent, removable and non-removable media that can be implemented by any method or technology to store information. The information can be computer-readable instructions, data structures, modules of programs or other data. Examples of computer storage media include, but are not limited to, phase change memory (PRAM), static random access memory (SRAM), dynamic random access memory (DRAM), other types of random access memory (RAM), read-only memory (ROM), electrically erasable programmable read-only memory (EEPROM), flash memory or other memory technology, read-only compact disk read-only memory (CD-ROM), digital versatile disk (DVD) or other optical storage, magnetic cassettes, magnetic tape magnetic disk storage or other magnetic storage devices or any other non-transmission media that can be used to store information that can be accessed by a computing device.
[0128] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for optimizing the design and manufacturing of a corrosion-resistant alloy structure of a dock folding device, characterized in that: The method comprises: Through numerical simulation methods, the evolution of alloy cross-section microstructure in seawater is captured; By adjusting the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions are calculated to measure the corrosion resistance of the alloy; Establish the quantitative relationship between alloy microstructure, surface free energy and corrosion resistance; Screening alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy to obtain target microstructure parameters and target surface free energy parameters of the alloys; According to the target microstructure parameters, using preset 3D printing conditions, constructing an alloy having a target microstructure through metal 3D printing; Using a preset pretreatment condition, a dense oxide film is modified on the surface of the alloy by a pretreatment method; Using preset fluorosilane modification conditions, the alloy with the oxide film is modified by fluorosilane, thereby preparing a super-hydrophobic alloy; The microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy; The alloy preparation conditions are optimized according to the influence rules.
2. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 1 is characterized in that: The alloy includes one or more of aluminum alloy, copper alloy, stainless steel and titanium alloy.
3. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 2 is characterized in that: The numerical simulation method includes a molecular dynamics simulation method and a finite element simulation method.
4. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 3 is characterized in that: The corrosion environment and stress boundary conditions include corrosion medium, temperature, and stress boundary conditions.
5. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 4 is characterized in that: The pretreatment method includes at least one of micro-arc oxidation, anodic oxidation and hydrothermal oxidation; the fluorosilane includes perfluorooctyltriethoxysilane or perfluorodecyltrichlorosilane.
6. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 5 is characterized in that: The microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy are detected by detection equipment, including: Detecting the microstructural parameters of the super-hydrophobic alloy by scanning electron microscopy or metallographic microscopy; The functional group content and the oxide film composition parameters of the super-hydrophobic alloy are detected by X-ray photoelectron spectrometer, X-ray diffractometer and infrared spectrum; The seawater contact angle and surface free energy of the superhydrophobic alloy are tested by a contact angle tester.
7. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 6 is characterized in that: The method further comprises: The corrosion resistance of the super-hydrophobic alloy is tested by a salt spray full immersion test and an electrochemical test, and the charge transfer resistance is characterized by testing and simulating the electrochemical impedance spectroscopy of different super-hydrophobic alloys; The steady-state electrochemical behavior was analyzed by potentiodynamic polarization test, and the corrosion potential, corrosion current density, cathode Tafel slope, and anode Tafel slope parameters of different superhydrophobic alloys were compared. Analyze the influence of hydrophobicity on corrosion behavior, and thus obtain the correlation between alloy construction method-microstructure, surface free energy-hydrophobicity-corrosion resistance; The target preparation conditions are optimized according to the correlation.
8. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 7 is characterized in that: A 3.5% by mass NaCl solution with a pH of 8 was used to simulate the seawater environment as the corrosion resistance test medium for the electrochemical test.
9. The corrosion-resistant alloy structure optimization design and manufacturing method according to claim 8, characterized in that: The method further comprises: By adjusting the heat source and process parameters to change the solidification condition of the alloy microstructure, or by changing the scanning strategy and forming angle to induce the formation of different microstructure orientations, the relationship between process parameters-microstructure-wear resistance and strength is analyzed, and combined with the plastic failure mechanism of the microstructure, the microstructure is induced with performance as the goal, thereby achieving in-situ enhancement of wear resistance and strength.
10. A corrosion-resistant alloy structure optimization design and manufacturing system for a dock folding device, characterized in that: The system comprises: Numerical simulation module, which captures the evolution of alloy cross-section microstructure in seawater through numerical simulation methods; The module for establishing the quantitative relationship of corrosion resistance calculates the corrosion potential, corrosion current density and charge transfer resistance of the alloy under different conditions by regulating the alloy microstructure, surface free energy parameters, corrosion environment and stress boundary conditions, which is used to measure the corrosion resistance of the alloy; establishes the quantitative relationship between the alloy microstructure, surface free energy and corrosion resistance; The target parameter acquisition module screens alloys with high corrosion potential and low corrosion current density and their corresponding microstructures and surface free energy, and obtains the target microstructure parameters and target surface free energy parameters of the alloys; A 3D printing module, according to the target microstructure parameters, uses preset 3D printing conditions to construct an alloy with a target microstructure through metal 3D printing; A pretreatment module, using preset pretreatment conditions and a pretreatment method to modify a dense oxide film on the surface of the alloy; A modification module, using preset fluorosilane modification conditions to modify the alloy with the oxide film by fluorosilane, thereby preparing a super-hydrophobic alloy; The detection module detects the microstructure parameters, functional group content, oxide film composition, seawater contact angle and surface free energy of the super-hydrophobic alloy through the detection equipment; thereby analyzing the influence of 3D printing conditions, pretreatment conditions and fluorosilane modification conditions on the microstructure, surface free energy and hydrophobicity of the alloy; The optimization module optimizes the alloy preparation conditions according to the influencing rules.
Citation Information
Patent Citations
Preparation method of ceramic-based composite coating capable of resisting seawater cavitation erosion
CN107130202A
Preparing method of wear-resisting hydrophobic coating
CN108468013A
Corrosion-resistant metal porous material and preparation method and application thereof
CN111910166A
Corrosion-resistant ultrahigh-strength steel for ocean platform and preparation method of corrosion-resistant ultrahigh-strength steel
CN116043105A
High-strength corrosion-resistant marine large rudder horn and casting process thereof
CN118222905A
Cited By
Forming processing method of high-corrosion-resistance copper bar for electrolytic bath
CN120797016A